Comparative Study Of Ketamine Versus Dexmedetomidine As An Adjunct For Transversus Abdominis Plane (TAP) Block For Cesarean Sections - Atif, Muhammad; Hussain, Mansoor; Farooq, Muhammad Umar; Hussain, Aftab; Wazir, Masood; Ayub, Maria (Journal of Rawalpindi Medical College, 2025)
Objective: To compare the efficacy of adding dexmedetomine versus ketamine to bupivacaine for TAP block in terms of postoperative pain score, rescue analgesia requirements and postoperative nausea and vomiting. Methodology: The study was a Quasi-experimental study, conducted in the Anesthesia Department, Tertiary Care Hospital from July to December 2023. We selected 120 patients scheduled for cesarean section and randomly divided them into two groups. At the end of surgery, group BD patients received a total volume of 40 ml, 20 ml on each side. This volume consisted of bupivacaine 0.125% with 0.5mcg/kg dexmedetomine. On the other hand, group BK patients received the same amount of volume on each side but instead of bupivacaine and dexmedetomidine we used bupivacaine 0.125% and ketamine 1 mg/kg. All patients were observed for post-op pain for 16 hours using a visual analogue scale. The need to give rescue analgesia was also recorded. Post-op vomiting was also noted. Results: Both groups were comparable in terms of visual analogue scale scores at 4, 8, 12 and 16 hours post-operatively with a p-value of 0.462, 0.295, 0.848 and 0.154 respectively. In group BD out of 60 patients, only 12 (20%) patients required rescue analgesia, whereas in group BK 16 (26.67%) patients were given rescue analgesia (p-value 0.388). In group BD, out of 60 only 3 (5%) patients had vomiting, whereas in group BK it was seen in 7 (11.67%) patients (p-value 0.186). Conclusion: It is concluded in our study that the addition of dexmedetomidine or ketamine to bupivacaine for transvesus abdominis plane block is equally effective and may provide effective analgesia at least for 16 hours. Keywords: Adjuncts, Bupivacaine, Dexmedetomidine, ERAS, Ketamine, Nerve block, Cesarean section.